Barriers and facilitators to deprescribing of cardiovascular medications: a systematic review - Nicolas Rodondi; Carole Elodie Aubert; Laureline Brunner (BMJ Open)
Objective To synthesise the current knowledge on barriers and facilitators to deprescribing cardiovascular medications (CVMs) at the levels of patients, informal caregivers and healthcare providers (HCPs).Design/setting We conducted a systematic review of studies exploring/assessing patient, informal caregiver and/or HCP barriers and/or facilitators to deprescribing CVMs.Data sources Ovid/MEDLINE and Embase from January 2003 to November 2021.Data extraction and synthesis We performed a deductive thematic analysis based on the framework of specific barriers and facilitators to deprescribing CVMs created by Goyal et al. We added a quantification of the occurrence of categories and themes in the selected articles to identify the resounding themes that indicate the greater impetus to address in future research.Results Most frequent deprescribing barriers for patients, informal caregivers and HCPs included uncertainty due to lack of evidence regarding CVM deprescribing (in n=10 studies), fear of negative consequences following deprescribing (n=13) and social influences (n=14). A frequently reported facilitator to deprescribing, especially for patients and informal caregivers, was the occurrence of adverse drug events (n=7). Another frequently reported facilitator for patients were dislike of CVMs (n=9). Necessity and benefit of CVMs were seen as barriers or facilitators similarly by patients and HCPs.Conclusion The differences in patient, informal caregiver and HCP regarding barriers and facilitators to deprescribing CVMs stress the need for ground discussions about beliefs and preferences of each stakeholder implicated in deprescribing decisions. Furthermore, HCP uncertainty regarding CVM deprescribing highlights the need to provide HCPs with tools that enable sharing the risks and benefits of deprescribing with patients and ensure a safe deprescribing process.PROSPERO registration number CRD42020221973.